Cleaner Production Implementation In An E-Waste Recovery Plant By Using The Value Stream Mapping - Ishak, Anuar; Mohamad, Effendi; Sukarma, Lukman; Salleh, Mohd Shukor; Salleh, Mohd Rizal; Mohamad, Noraiham; Raja Abdullah, Raja Izamshah; Md Ali, Mohd Amran (Penerbit Universiti, UTeM, 2018)
This study aims to determine the manner in which the Cleaner Production (CP) sustainability measures would be embedded into the altered Value Stream Mapping (VSM), which is a Lean Manufacturing tool. The typical VSM technique does not consider the societal and the environmental metrics that are imperative for determining the sustainability for any production line. Additionally, the Guidelines for Green Industry Auditor, 2014, published by the Department of Environment, Malaysia, have made no mention regarding the proper lean tools which need to be applied to the audit systems as per the USEPA for improving the system. The VSM ability to determine the environmental, economic and societal performance would help VSM be a useful tool. Also, many companies can apply the data generated in a better manner and change their operations to fit the technology for improving the manufacturing. This paper has presented a CP implementation with the help of a VSM technology, based on the earlier literature. One pilot case study has been conducted in the local e-Waste Recovery Plant, ABC Sdn. Bhd., which demonstrated that this VSM approach, could capture the environmental, economic and societal sustainability for a specific process and has also, recommended some future researches.